Prehospital Care by Telegraphic Medicine System for Advanced Emergency Medical Service at Maharat Nakhon Ratchasima Hospital - Chinprasatsak, Soontorn; Satthaphong, Supralerk; Maporn, Kunakorn (Journal of Health Science of Thailand, 2017)
There have been an average of 54,000 critical-level services outside the hospital of Emergency Medical Service Unit in Nakhon Ratchasima Province each year, resulting in 1,800 deaths prior to hospital arrival. Although the medical services outside the hospital has been continually improved, most systems are not suitable in practice. Maharat Nakhon Ratchasima Hospital (MNRH) developed an information system for seamless emergency services outside the hospital, the telegraphic medicine system, for caring and referring critical patients between hospitals. The objective of this study was to assess the efficiency and the use of the telegraphic medicine system. It was conducted as a prospective analytical study during October 2014 to March 2015. Appropriateness of the services was compared between patients recieving services from the medical care team with or without physician in an ambulance with and without the telegraphic medicine. The study samples were 100 emergency patients. Data were collected from the emergency service record forms. It was found that there was no statistical difference of the appropriateness of the care of the emergency patients if there was an available physician in the ambulance team (p>0.05) . In case of the unavailable physician, the ambulance with telegraphic medicine system was found to be significantly more appropriate for respiratory care, circulatory care, neurological care and other additional medical care (p<0.05). Thus, the telegraphic medicine system is useful for caring critical patients outside hospital when lacking of attending physician.